Emotion and forced migration. A biographical and metaphor analysis of the ‘GDR children from Namibia’ (Journal of Namibian Studies : History Politics Culture, 2022)
Forced migration is a complex process fraught with emotion. Biographical interviews offer limited scope for translating this process into narratives, yet it is nevertheless reflected in the material in various ways, such as through metaphors. We used interviews and observational material from a qualitative, empirical research project on the “GDR children from Namibia” to explore an analytical procedure that links the reconstruction of narrated and lived biographies (in German: erzählte and erlebte Lebensgeschichte) with reconstructive metaphor analysis. This allowed us to capture the actor’s emotional experience via metaphors without losing sight of the complexity of biographical reconstruction.